Performance analysis on wideband fast Fourier transform spectrometer of THz atmospheric limb Sounder (TALIS). (November 2021) - Xu, Haowen; Lu, Hao; Wang, Zhenzhan; Wang, Wenyu; He, Wenming; Xiao, Yuwei
Highlights: Fast Fourier transform spectrometer can perform fine spectral analysis. Core algorithm has no effect on brightness temperature measurements. Correlation of power spectrum becomes lower as the quantization bits decrease. Brightness temperature biases become larger as the quantization bits decrease. Low-order quantization below 3-bit will cause the deterioration of the sensitivity. Abstract: THz Atmospheric Limb Sounder (TALIS) is a terahertz band microwave radiometer used to sound the vertical distribution of the atmosphere, focusing on the distribution of trace gases. The back-end fast Fourier transform spectrometer (FFTS) is the core component of TALIS and will be used for the first time in the limb sounding. The radix 16 real-time complex FFT algorithm is the core algorithm of the FFTS. Each FFTS has a bandwidth of 2 GHz and a spectral resolution of 2.3 MHz. In this study, the improved error evaluation of the core algorithm and the multi-perspective analysis of the quantization bits are introduced. The results show that brightness temperature bias, with a maximum value of about 0.02 K, will be caused by the core algorithm. As the quantization bits decrease, the correlation of the power spectrum decreases and the brightness temperature biases at the peaks increase. Compared with the ideal quantization, the overall correlation coefficients of the power spectrum for 3-bit and greater quantization are above 0.9999, the maximum brightness temperature biases are approximately 0.08 K, 0.3 K, 1.2 K, 4.4 K, 9.5 K, and 21 K, corresponding to the 10-bit, 8-bit, 6-bit, 4-bit, 3-bit, and 2-bit quantization, and the 3-bit and 2-bit quantization will lead to a deterioration of TALIS sensitivity by about 2% and 12%, respectively. The research in this study will provide an important reference for the scientific design of TALIS, and it will provide vital practical significance for the implementation of more channels of the FFTS.